Effect of Menstruation on Education Among Bachelor-Level Female Students in Kathmandu Valley - Upadhya Adhikari, Shanta; Adhikari, Anup (Education Quarterly, 2024)
The study titled “Effect of Menstruation on Education among Bachelor level female students in Kathmandu Valley” investigates the impact of menstruation on the education of young women in Kathmandu Valley. It aims to highlight the health challenges encountered during menstruation and how these hurdles affect academic pursuits. Menstruation is a natural biological process that recurs monthly in females and is governed by hormonal fluctuations. This quantitative study employs a descriptive methodology, with a sample size of 250 respondents chosen randomly. Ethical protocols were upheld to safeguard confidentiality and obtain informed consent. Data collection took place across two campuses within Kathmandu Valley. The findings emphasize prevalent challenges: inadequate access to hygienic sanitary products, limited disposal facilities, and insufficient privacy for changing sanitary materials. Furthermore, the lack of clean water exacerbates hygiene concerns. These findings underscore the need for comprehensive menstrual health initiatives to ensure the well-being and education of young women.